Dinamika Quarter Life Crisis pada Mahasiswa dalam Perspektif Kawruh Jiwa Ki Ageng Suryomentaram - Zharifa, Farahdita Salma; Magistravia, Esa Geniusa Religiswa; Febrianti, Rizky Amelia; Jati, Riskhi Pratama Kusuma Arum; Maharani, Septiana Dwiputri (Jurnal Filsafat Indonesia, 2023)
Quarter Life Crisis is a crisis that is often experienced in emerging adulthood. College students are one of the most vulnerable to this crisis due to various difficulties in the current era. This study examines the dynamics of the quarter life crisis faced by Yogyakarta students and looks at this crisis with Kawruh Jiwa Ki Ageng Suryomentaram perspective's which contains the values ​​and philosophical concepts of Indonesian society. This research also examines alternative solutions of the quarter life crisis based on the Ki Ageng Suryomentaram perspective. The research method is phenomenological qualitative research and library research. The results of this study show that individuals in quarter life crisis feel anxiety about their life followed by some typical behaviors that affect self-functioning. According to Suryomentaram's perspective, the quarter life crisis is related to "Rasa '' and "Karep '' which Mulur mungkret (raise-shrink) causes Bungah (happy) and Susah (Sad). Coping with the quarter life crisis is about self-regulation which in Ki Ageng Suryomentaram is focused on " Pangawikan Pribadi" and "Mawas Diri".